Importance of the dentist in early diagnosis of pemphigus vulgaris - Thiago de Santana Santos; Marta Rabello Piva; Paulo Nand Kumar; Paulo Ricardo Saquete Martins Filho; Daniele Machado Reinheimer; Carla Renata Acevedo (Faculdade São Leopoldo Mandic, 2009)
The vulgar pemphigus is a chronic, rare, vesicle-bubble disease of autoimmune origin and with a possibility of following a dangerous clinical course when it is not diagnosed and treated in its initial stage. It usually affects people from 40 to 60 years old, being rare in children. In the majority of cases, oral manifestations are the first signs of the disease, so that dentists play an important rol in its early diagnosis. The authors present a case report of vulgar pemphigus in a 17 year-old patient, attended by the Bucco-Maxillo-Facial Surgery Service of the "Fundação de Beneficência Hospital de Cirurgia" in Aracaju-SE, Brazil. The patient was admitted with a complaint of the presence of numerous scattered painful ulcers in the mouth that had developed in approximately two months, and reported that at first, blisters that broke quickly appeared, leading to extremely painful ulcerations. Incisional biopsies were performed in the jugal mucosa and retromolar regions, and also a complete hemogram to discard the hypothesis of leukemia. In view of the clinical and histopathological findings, the final diagnosis of pemphigus vulgaris was made. Before receiving specialized treatment, the patient presented marked worsening of the clinical condition, with exacerbation of intraoral signs and symptoms and development of skin lesions around the body surface. The patient was hospitalized in the "Hospital Universitário da Universidade Federal de Sergipe" and treated with prednisone, cimetidine and nystatin, showing significant improvement of symptoms in approximately two weeks. At present, the patient is under the care of an interdisciplinary team that includes dermatologists and dentists.